2010
DOI: 10.1093/sleep/33.11.1465
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Sleep Deprivation: Shifts in Regional Brain Activity and Learning Strategy

Abstract: together, these findings suggest that the brain compensates for negative effects of sleep deprivation on the hippocampal memory system by promoting the use of a striatal memory system. However, effects of sleep deprivation can still appear later on because the alternative learning mechanisms and brain regions involved may result in reduced flexibility under conditions requiring adaptation of previously formed memories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 48 publications
7
76
0
Order By: Relevance
“…We found that sleep deprivation following training during the late day impaired the consolidation of LTM. This is consistent with previous research in rodents demonstrating that posttraining sleep deprivation interferes with LTM 7,45,[88][89][90][91][92] and studies in Drosophila. 6,93 In contrast, when sleep deprivation occurred after the period of macromolecular synthesis necessary for 24 h memory, we found that long-term LFI memory was unaffected by sleep deprivation.…”
Section: Discussionsupporting
confidence: 93%
“…We found that sleep deprivation following training during the late day impaired the consolidation of LTM. This is consistent with previous research in rodents demonstrating that posttraining sleep deprivation interferes with LTM 7,45,[88][89][90][91][92] and studies in Drosophila. 6,93 In contrast, when sleep deprivation occurred after the period of macromolecular synthesis necessary for 24 h memory, we found that long-term LFI memory was unaffected by sleep deprivation.…”
Section: Discussionsupporting
confidence: 93%
“…Together, these findings support the notion that secondary working memory training has potential value to increase attentive performance on targeted tasks and skills despite extensive practice and experience (e.g., Di Nocera et al 2006;Youmans and Ohlsson 2008;Hagewoud et al 2010;Friederich and Herzog 2011;Gillan et al 2011;He et al 2011;Reichenbach et al 2011;Hogarth et al 2013). Consistent with this hypothesis, delay discounting has been shown to improve both with working memory training and instruction that shifts attention to focus on later rather than immediate rewards (Radu et al 2011).…”
Section: Discussionsupporting
confidence: 66%
“…A consistent finding in these studies is that the hippocampus-dependent version is more age-sensitive than the nonhippocampus-dependent version. Switches in learning strategy are also seen with sleep deprivation, which has adverse effects on hippocampus-dependent memory formation (Hagewoud et al 2010;Havekes et al 2011). We suspect that cTPL requires the plasticity of an intact hippocampus, while instead ordinal (noncircadian) TPL may depend more on a less age-sensitive memory system, presumably the striatum (Mulder et al 2013b).…”
Section: Switching Strategiesmentioning
confidence: 99%